Resilience and resolve communities against terrorism - Jerard, Jolene; Nasir, Salim Mohamed (Imperial College Press insurgency and terrorism series, 2015)
This book aims to provide an overview of the importance of communities to mitigate the threat of terrorism, drawing key lessons and experiences from countries adopting community-based approaches.